Implementasi Model Pembelajaran Student Teams Achievement Division Pada Mata Pelajaran Instalasi Motor Listrik - Putri, Ira Jefiarni; Asnil, Asnil (Jurnal Pendidikan Teknik Elektro, 2024)
This research was conducted to analyze the implementation of the Student Teams Achievement Division (STAD) learning model to improve the learning outcomes of vocational high school students in the subject of Electric Motor Installation. The method used is a quantitative analysis. This research employs an experimental method in the form of True Experimental Design. The research uses pretest and posttest questions in objective form to assess students' learning outcomes, and these are tested using validity tests, reliability tests, differentiation tests, and question difficulty indices to determine the suitability of the instruments used. The results of the pretest and posttest are analyzed using learning https://ej.ejsst.com/ outcome completeness, and effect size. and analysis of students' learning activities. The research findings indicate that the implementation of the Student Teams Achievement Division (STAD) learning model in the Electric Motor Installation subject can improve students' learning outcomes. This can be seen from the pretest and posttest results, where the analysis of learning outcome completeness shows that many students meet the minimum completeness criteria set by the school. Additionally, the effect size analysis shows a significant impact of the use of e-modules in enhancing students' learning outcomes. and the analysis of student activities shows that the percentage falls into the very high category with the use of the STAD learning model.